Профессиографический анализ деятельности специалиста как источник формирования учебного материала - Ашеров, Акива Товиевич; Горбатюк, Лариса Васильевна; Самойлова, Екатерина Владимировна (НТУ "ХПИ", 2010)
This article compares the possibility of educational qualification characteristics of graduate and professiograme (job description) as sources of requirements for the forming of content of the material for modernized or new disciplines. The substantiation of goals, structure, content and methods of development of such professiogrames, which orient on training, are given.
Keywords: профессиографический анализ; профессиональная деятельность специалиста; профессиограмма